Diversity and natural selection on the thrombospondin-related adhesive protein (TRAP) gene of Plasmodium knowlesi in Malaysia - Ahmed, Md Atique; Lau, Yee Ling; Quan, Fu-Shi (BioMed Central, 2018)
Background: Plasmodium knowlesi a parasite of the macaques is currently the most common cause of human malaria in Malaysia. The thrombospondin-related adhesive protein (TRAP) gene is pre-erythrocytic stage antigen. It is a well-characterized vaccine candidate in Plasmodium vivax and Plasmodium falciparum, however, no study has been done in the orthologous gene of P. knowlesi. This study investigates nucleotide diversity, haplotypes, natural selection and population differentiation of full-length pktrap genes in clinical samples from Malaysia. Methods: Forty full-length pktrap sequences from clinical isolates of Malaysia along with the reference H-strain were downloaded from published databases. Genetic diversity, polymorphism, haplotype and natural selection were determined using DnaSP 5.10 software. McDonald-Kreitman test was conducted using P. vivax and Plasmodium coatneyi as ortholog sequence in DnaSP 5.10 software. Population genetic differentiation index (F ST ) of parasite populations was determined using Arlequin v3.5. Phylogenetic relationships between trap ortholog genes were determined using MEGA 5.0 software. Results: Comparison of 40 full-length pktrap sequences along with the H-strain identified 74 SNPs (53 non-synonymous and 21 synonymous substitutions) resulting in 29 haplotypes. Analysis of the full-length gene showed that the nucleotide diversity was lower compared to its nearest ortholog pvtrap. Domain-wise analysis indicated that the proline/asparagine rich region had higher nucleotide diversity compared to the von Willebrand factor domain and the thrombospondin-type-1 domain. McDonald-Kreitman test identified that the ratio of the number of nonsynonymous to synonymous polymorphic sites within P. knowlesi was significantly higher than that of the number of nonsynonymous to synonymous fixed sites between P. knowlesi and P. vivax. The von Willebrand factor domain also indicated balancing selection using MK test, however, it did not give significant results when tested with P. coatneyi as an outgroup. Phylogenetic analysis of full-length genes identified three distinct sub-clusters of P. knowlesi, one originating from Peninsular Malaysia and two originating from Malaysian Borneo. High population differentiation values was observed within samples from Peninsular Malaysia and Malaysian Borneo. Conclusions: This study is the first to report on the genetic diversity and natural selection of full-length pktrap. Low level of genetic diversity was found across the full-length gene of pktrap. Balancing selection of the von Willebrand factor domain indicated that TRAP could be a target in inducing immune response against P. knowlesi infections. However, higher number of samples would be necessary to further confirm the findings.